PERFORMING ARTS CENTER AS COLLABORATION SPACE AT SRIWEDARI, SURAKARTA - Ghozali, Ahmad
The city of Surakarta is known as a cultural city that has cultural diversity that must be developed and preserved. The success of developing traditional arts is highly dependent on existing human resources, namely the art community. However, the art community in Surakarta tends to be fragmented and move independently. This has resulted in limited and less optimal art development efforts. As an effort to create a movement of togetherness between existing art communities, an integrated forum is needed as a means for creating and collaborating between art communities. This integrated platform is implemented by providing a performing arts center that can provide space for artists and the art community to interact with each other. This project is designed to accommodate 3 main functions, which are the performing arts and culture function, community function, and recreation. The concept for the design of the performing arts center raises the wisdom of local cultural values combined with the development of contemporary architecture that develops in society to provide an art space capable of supporting interactions between artists and art activists as an effort to create a collaborative climate in the effort to preserve and develop traditional performing arts. From the big concept, then derived into 3 aspects in the design, which are the moderntraditional building design, social interaction, and collaboration. Traditional-modern is manifested by the use of Javanese traditional philosophy and elements combined with current technological developments. Furthermore, the aspect of social interaction is implemented by providing spaces that are able to accommodate various activities to increase interaction between communities. Then the collaboration aspect is implemented by providing spaces that are able to increase interaction between artists and artists with art enthusiasts to create a collaborative climate and encourage collaboration between artists.